Aleksei P. Okladnikov : the great explorer of the past. - Konopat͡skiĭ, A. K. (Archaeopress Publishing Ltd., 2019)
Aleksei P. Okladnikov (1908-1981) was a prominent archaeologist who spent more than 50 years studying prehistoric sites in various parts of the Soviet Union - mainly in Siberia and Central Asia as well as in Mongolia. Okladnikov made numerous fascinating discoveries in the 1930s, including the first Neanderthal remains in the USSR at Teshik Tash (Uzbekistan) and unique figurines at the Upper Palaeolithic site of Buret' in the Angara River basin (Eastern Siberia). His research and achievements are presented on the background of ideological campaigns inspired by the Communist Party in the 1920s-1950s, a subject that is very rarely described in non-Russian sources. Particular attention is given to the debunking of the 'Japhetic theory' and the 'new doctrine of language' developed by Nikolai Y. Marr, an Oriental scholar and specialist in languages who in the 1920s-early 1930s was a formal leader of Soviet archaeology.